Personal memory and the negotiation of identity : a self portrait - Pratt, Sarah Jane (Michaelis School of Fine Art, 2017)
The first section of this paper surveys the differing characteristics of memory, its fragmentary qualities, its constant negotiation within the present, its personalised form and its links to identity-formation and construction. Concepts of continuity, stabilising identity within the present, and their corresponding memory-related problems are discussed. Photographs are looked at in relation to memory as well as for their ability to inform or influence individual identity. References to the multi-faceted information that is unconsciously assimilated from multi-media sources in today's society, and the resultant identity related complexities introduce a more personal outlook on historically specific factors that appear to have destabilised identity. The Truth and Reconciliation Commission is briefly introduced from the perspective of recreating one collective national memory and the implicit complexities involved on both a personal and collective level. Section two of the paper establishes the importance of place in the formation of identity and then looks specifically at historical incidents that are relevant to my personal self-consciousness. Zimbabwean land reform issues, political racism and economic problems are presented as occurrences powerful enough to trigger the conscious scrutiny of identity and a personal sense of the past. Travel-related experiences are discussed with issues pertaining to the destabilisation felt when the individual is introduced to "other" discourses or cultures. Exposure to these occurrences, and conjecture surrounding their "ripple effect" on the individual provide the starting point from which to understand the motivation behind my body of practical work. The third section of this paper looks closely at the problems, possibilities and variations involved in making a body of work around the concept of personal memory. The history of etching is briefly discussed, and the method of etching is compared to the recollection process. Finally, the panel of work is presented as a "heritage site" to the viewer, and a form of re-evaluation of identity for the maker. A series of narrative texts are sourced as personal springs that triggered the production of each image, and serve to accompany or enrich the artworks themselves.